Perspektywy rozwoju firm ochroniarskich jako zleceniobiorców usług outsourcingowych na przykładzie Agencji Ochrony "Hektor" - Zakrzewski, Marek (My University, 2015)
Obecnie wiele firm korzysta z usług outsourcingowych. Łączenie najwyższej jakości z jak największą minimalizacją kosztów to praktycznie cel każdej firmy, a outsourcing jest narzędziem pozwalającym to wykonać. W uproszczeniu outsourcing polega na przekazaniu czynności, które wykonywali pracownicy danego przedsiębiorstwa firmie zewnętrznej. Outsourcing jest alternatywą, która może być korzystniejsza niż dotychczasowe rozwiązania. Celem outsourcingu jest zwiększenie skuteczności i efektywności prowadzonej działalności. Celem pracy jest analiza metod oceny efektywności outsourcingu z punktu widzenia jego przydatności. Z outsourcingu w zakresie ochrony korzysta około 75% podmiotów działających dziś na polskim rynku. Autor stawia tezę, że wdrażanie projektów outsourcingowych wymaga szczegółowych procedur i znajomości branży, rynku i specyfiki pracy, jaką jest branża ochroniarska. Niniejsza praca definiuje metody outsourcingowe i prezentuje ich zastosowanie na przykładzie projektu.

Nowadays a lot of companies use outsourcing services. Connecting high quality with lowering the costs as much as possible is the purpose of each company and outsourcing is a tool which enables to do so. Generally speaking, outsourcing focuses on transferring an action which used to be performed by the workers of a particular company onto an external company. That is why, it is an option which can be more profitable for the company than solutions that have been used so far. The purpose of outsourcing is to increase effectiveness and efficiency of a business . The thesis aims at analysing the methods of evaluation how efficient outsourcing is from the viewpoint of its usefulness. Approximately 75% of economic entities on the Polish market in the in the field of security guard services take advantage of outsourcing . The author of the thesis argues that implementing outsourcing projects requires detailed procedures as well as extensive knowledge concerning the subject of security guard service business. This thesis defines the methods of outsourcing and presents their use on the basis of an investment project .
Development prospects of security guard agencies as outsourcing services contractors: the case of Security Guard Agency “Hektor”
Keywords: outsourcing; Agencja Ochrony Hektor; analiza SWOT; analiza strategiczna; usługi ochroniarskie; outsourcing (abbrev. outside-resource-using); Security Guard Agency “Hektor”; SWOT analysis; strategic analysis; security guard services